Minkowski Spacetime: A Hundred Years Later - Petkov, Vesselin; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
This volume is dedicated to the one hundredth anniversary of the publication of Hermann Minkowski's paper "Space and Time" in 1909. His work on the spacetime representation of special relativity had a huge impact on the twentieth century physics to the extent that modern physics would be impossible without the notion of spacetime. While there is consensus on the mathematical significance of spacetime in theoretical physics, for a hundred years there has been no consensus on the nature of spacetime itself. We owe Minkowski a clear answer to the question of the nature of spacetime -- whether it is only a mathematical space or represents a real four-dimensional world. A century after its publication the original Minkowski paper still represents an enrichment to the physicists, especially the relativists, who read it with the intent to fully investigate the depth of Minkowski's ideas on space and time and the physical meaning of special relativity. The volume begins with an excellent retranslation of Minkowski's paper by Dennis Lehmkuhl, accompanied by the original German version of the article. The fourteen contributions are divided into three parts entitled "The Impact of Minkowski Spacetime on the Twentieth Century Physics from a Historical Perspective", "Implications of Minkowski Spacetime for Theoretical Physics", and "Conceptual and Philosophical Issues of Minkowski Spacetime."
The Impact of Minkowski Spacetime on the Twentieth Century Physics from a Historical Perspective -- Hermann Minkowski, Relativity and the Axiomatic Approach to Physics -- Minkowski$1 (Bs Modern World -- Implications of Minkowski Spacetime for Theoretical Physics -- Hermann Minkowski and Special Relativity -- The Rich Structure of Minkowski Space -- Minkowski Space-Time and Quantum Mechanics -- Modern Space-Time and Undecidability -- Quantum Space-Times -- Space-Time Extensions in Quantum Gravity -- Conceptual and Philosophical Issues of Minkowski Spacetime -- The Adolescence of Relativity: Einstein, Minkowski, and the Philosophy of Space and Time -- Hermann Minkowski: From Geometry of Numbers to Physical Geometry -- The Mystical Formula and The Mystery of Khronos -- Physical Laws and Worldlines in Minkowski Spacetime -- Time as an Illusion -- Consequences of Minkowski$1 (Bs Unification of Space and Time for a Philosophy of Nature.s
Keywords: Physics; Science -- Philosophy; Physics; History and Philosophical Foundations of Physics; Philosophy of Science